The difference of the gingival condition between diabetes mellitus and non diabetes mellitus patient on children at Cipto Mangunkusumo Hospital Jakarta - Maulani, Wilda Kemala; Gartika, Meirina; Hendiani, Ina (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Diabetes mellitus is a systemic condition that affected the periodontium condition. The purpose of the research was to find the difference of the gingival condition between diabetes mellitus and nondiabetes mellitus patient on children at Cipto Mangunkusumo Hospital (RSCM) Jakarta. The research method was descriptive comparative. The sample consists of 20 children with diabetes mellitus and 20 children nondiabetes mellitus used purposive sampling. The gingival condition was scored by using Loe and Silness Gingival Index. The research showed that the average of the gingival index in diabetes mellitus children was 1.1250 and nondiabetes mellitus was 0.9562. The statistic analysis was t-Test and the Î± was 5% showed that there was a significant difference gingival condition between diabetes mellitus patient and nondiabetes mellitus patient on children. Conclusion showed a difference gingival condition between diabetes mellitus patient with nondiabetes mellitus patient on children at RSCM Jakarta, the gingival condition of diabetes mellitus patient on children was more severe than nondiabetes mellitus patient.